Insomnia predicts treatment engagement and symptom change: a secondary analysis of a web-based CBT intervention for veterans with PTSD symptoms and hazardous alcohol use. Issue 1 (31st August 2021) - Buckheit, Katherine A; Nolan, Jon; Possemato, Kyle; Maisto, Stephen; Rosenblum, Andrew; Acosta, Michelle; Marsch, Lisa A
Abstract: Posttraumatic Stress Disorder (PTSD) and hazardous drinking are highly comorbid, and often more severe than PTSD or hazardous drinking alone. Integrated, web-based interventions for PTSD/hazardous drinking may increase access to care, but have demonstrated equivocal results in reducing PTSD and hazardous drinking. One factor that may explain treatment engagement and symptom change is the presence of insomnia symptoms. The current study conducted secondary data analysis of a randomized controlled trial of an integrated web-based intervention for PTSD symptoms and hazardous drinking to examine insomnia symptoms as predictors of PTSD symptoms, alcohol use, and treatment engagement. In the parent study, 162 veterans in primary care reporting PTSD symptoms and hazardous drinking were randomized to receive either the intervention or treatment as usual. The current study examined insomnia among veterans who received the intervention ( n = 81). Regression models tested baseline insomnia symptoms as predictors of treatment engagement, follow-up PTSD symptoms, and alcohol use. Hierarchical regression models tested change in insomnia during treatment as a predictor of follow-up PTSD symptoms and alcohol use. Results showed baseline insomnia predicted treatment engagement and follow-up drinking days, but not PTSD symptoms or heavy drinking days. Although overall change in insomnia was small, it predicted follow-up PTSD and heavy drinking days, but not drinking days. Results are consistent with previous research highlighting the importance of identifying and treating insomnia in the course of integrated treatment for PTSD/hazardous drinking. Future research should investigate how to best integrate insomnia, PTSD, and/or hazardous drinking interventions to maximize treatment engagement. Abstract : Veterans in treatment for PTSD and alcohol use who had more insomnia symptoms completed less treatment. Those who improved their insomnia during treatment reported fewer PTSD symptoms and alcohol use.